Strategi Pemasaran Museum Buleleng Dalam Upaya Meningkatkan Jumlah Kunjungan Wisatawan - I Gede Putra Nugraha; Made Dian Putri Agustina (UNHI Press, 2020)
This study aims to describe the decrease factor of tourist visits to the Museum Buleleng, marketing strategies used to increase the number of tourist visits to the Museum Buleleng. This study used a SWOT analysis to identify strengths, weaknesses, opportunities, and threats in Buleleng Museum, and discussed using qualitative descriptive analysis. This research subject is the manager of the Buleleng Museum. Then the object of this study is data on the number of tourists. Data on the number of tourist arrivals was obtained through interviews with related parties. Data were analyzed descriptively. These results indicate that factors causing the decline in the number of tourist visits to the Museum Buleleng namely internal factors and external factors do not Buleleng Museum marketing strategy, which is due to funding constraints. Results of the analysis of the data showed that important to know the potential, weaknesses that should be corrected, an opportunity that must be exploited to the maximum, and a threat to be faced so that it can be known from the marketing strategy to be followed.